(3GdJOGhj HGdCYTGH hGdWH GdfHhjs (3OYhI ddJbfjf GdYdej dCYTGH GdWH GdfHhj hGdJQGK GdYQHjs - (3SjO, YHO GdHGSW eMeOs ((3GdLjRI, eUQs (3GdTQcI GdeUQjI GdYGdejI ddfTQ (B- (3dhfLeGfs, 2006)
(3jTed gPG GdcJGH hUaG ddfHGJGJ GdJi PcQJ ai GdWH GdfHhi hHYV fHGJGJ eUQ GdWHjI, hcPdc JbfjfkG YdejG dHYV gPg GdhUaGJ(B. (3ceG jHjf GdLhgQ h GdehGO GdaYGdI ajgG, hJCKjQ gPg GdehGO aGQeGchdhLjG(B. (3hjhVM GdcJGH CjVkG cjajI GdYdGL HGdJOdjc h GdZPGAs
(3eJhGaQ GdWHYI GdKGefI dYGe (B2006 (3HecJHI eHGQc aQY GdRjJhfs
(3eJhaQ ef GdcJGH GdWHYI GdJGSYI dYGe (B2017 (3HecJHI eUQ GdYGeI (B_ (3aQY YRHI GdHQLs
1 2 3 5 7 8 10 11 12 13 14 20 21
Keywords: (3GdWH GdfHhjs; (3GdYdGL HGdCYTGHs; (3GdfHGJGJ GdWHjIs